The Evolution of Research on Critical and Creative Thinking Skills in Education (2017-2026) : A Bibliometric Study - Sura Juddin; Prelia Dwi Amanah; Baiq Helmalya Roshita; Ferniawan (Science Education Doctoral Study Program, Postgraduate, Mataram University, 2026)
This study aims to analyze the evolution of research on critical thinking skills and creative thinking skills in education during the period 2017–2026 using a bibliometric approach. Data were collected from Google Scholar through Publish or Perish and Dimensions.ai and analyzed using VOSviewer to generate network, overlay, and density visualizations. The findings reveal a significant increase in publication output over the last decade, reflecting growing global interest in these competencies. Journal articles emerged as the dominant publication type, while education was identified as the leading research field. The results also indicate strong connections between critical thinking and creative thinking, with creativity, creative thinking, critical thinking skills, relationship, and higher education appearing as the most influential keywords. Visualization analyses demonstrate that these concepts form an interconnected knowledge structure and have increasingly been associated with educational innovation, digital transformation, and 21st-century skills development. Furthermore, the research themes show strong alignment with several Sustainable Development Goals (SDGs), particularly Quality Education. Overall, the findings suggest that critical thinking and creative thinking have evolved into complementary and multidisciplinary competencies that play a strategic role in education and human development. Future research should focus on integrating these competencies with emerging technologies and innovative learning environments.